Disease activity early in treatment as a predictor of future low disease activity in RA patients treated with iguratimod. Issue 2 (3rd March 2016) - Yoshioka, Yutaka; Takahashi, Nobunori; Kaneko, Atsushi; Hirano, Yuji; Kanayama, Yasuhide; Kanda, Hiroyasu; Takagi, Hideki; Ito, Takayasu; Kato, Takefumi; Saito, Kiwamu; Funahashi, Koji; Asai, Shuji; et al.
Abstract : Objectives. This retrospective observational study aimed to examine the efficacy of iguratimod with and without concomitant methotrexate (MTX) and to estimate the adequate observational period for predicting low disease activity (LDA) achievement at 24 weeks in patients with rheumatoid arthritis (RA). Methods. All patients treated with iguratimod were registered in a Japanese multicenter registry. Multivariate analyses were performed to identify predictive factors for LDA achievement at 24 weeks. Receiver operating characteristic (ROC) curve analyses were performed to estimate the association of 28-joint disease activity score based on erythrocyte sedimentation rate (DAS28-ESR) at each time point with achievement of LDA at 24 weeks and determine a cut-off for DAS28-ESR. Results. A total of 123 patients were treated with iguratimod with ( n = 65) or without ( n = 58) MTX. Iguratimod therapy resulted in significant clinical improvement in both groups. Multivariate analysis revealed that DAS28-ESR at each time point was an independent significant predictor of LDA achievement at 24 weeks. Cut-off values of DAS28-ESR at 12 weeks based on ROC curves were 3.2 and 3.6 in patients with and without MTX, respectively. Conclusions. Iguratimod was effective in RA patients in clinical practice. Our results suggest that 12 weeks may be a sufficient period to judge the medium-term efficacy of iguratimod in patients treated with and without MTX.